STUDY ON REDUCING AND MELTING BEHAVIOR OF MILL SCALE/PETROLEUM COKE BLEND - Bruno Deves Flores; Ismael Vemdrame Flores; Maurício Covcevich Bagatini; Eduardo Osório; Antônio Cezar Faria Vilela (Tecnologia em Metalurgia, Materiais e Mineração, 2015)
Self-reducing tests were carried out under isothermal and non-isothermal condition in a muffle furnace, aiming to assess the reduction and melting of a self-reducing blend of mill scale and petroleum coke (85-15% in weight). The products obtained were analyzed by mass loss and wet analysis. Further investigations for the products from the non-isothermal condition were done by X-ray diffraction, nude eye inspection and carbon analyzer. It was observed that mass loss fraction and metallization degree are directly related and both increase with time and temperature. In the non-isothermal maximum mass loss was achieved in 8 minutes, reaching metallization degrees above 90%. It was observed that the reduction of iron oxide occurs mainly in solid state and the smelting of the samples is directly related to the iron carburization process. Thus, the use of self-reducing mixtures shows a possible way to recycle mill scale.